Associations between ethnic-racial identity and alcohol problems among diverse emerging adults. Issue 2 (2nd May 2022) - Walker, Chloe J.; Derlan Williams, Chelsea; Cage, Jamie; DeLaney, Eryn N.; Lozada, Fantasy T.; ,; Dick, Danielle M.
Abstract: Excessive alcohol use and problems during college is a major public health concern, and there are health disparities in patterns of drinking and alcohol-related illnesses based on ethnicity and race. Given the prevalence and disparities in excessive alcohol use and problems and associated negative impacts, it is important to examine potential protective factors such as dimensions of ethnic-racial identity (ERI). Thus, the current study examined how multiple dimensions of ERI were associated with alcohol use and alcohol use disorder (AUD) symptoms, and how these relations varied by individuals' ethnic-racial group among 1850 diverse emerging adults ( M  = 18.46, SD = .38). Findings indicated that there were significant differences by race/ethnicity. ERI affirmation was negatively associated with AUD symptoms for Asian individuals and African American individuals, while ERI exploration was positively associated with AUD symptoms among African American individuals. ERI resolution was negatively associated with alcohol use for Latinx individuals and positively associated with alcohol use for Multiracial individuals. Among White individuals, ERI exploration was negatively associated with alcohol use and ERI affirmation was negatively associated with AUD symptoms. Overall, the current study builds on our understanding of nuanced ways in which ethnic-racial identity impacts alcohol problems among emerging adults and highlights areas for future research.